PENGARUH EARNING PER SHARE DAN NET PROFIT MARGIN TERHADAP HARGA SAHAM PADA PT INDOCEMENT TUNGGAL PRAKARSA TBK PERIODE 2010-2020 - Hendri Gunawan (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
This study aims to determine the effect of Earning Per Share and Net Profit Margin on Share Prices at PT Indocement Tunggal Prakarsa Tbk Period 2010 - 2020. The type of research used is quantitative research with samples in the form of financial statements in the form of balance sheets and profit and loss statements of PT Indocement Tunggal Prakarsa. Tbk period 2010-2020. The results of this study indicate that partially there is a significant influence between Earnings per Share (EPS) on Share Price on PT Indocement Tunggal Prakarsa Tbk. period 2010-2020.proven by the value of tarithmetic = 4.396 while ttable = 2.306 (tarithmetic > ttable) and strengthened by a significance level of 0.002 <0.5. Partially there is a significant influence between Net Profit Margin (NPM) on the stock price of PT Indocement Tunggal Prakarsa Tbk. period 2010-2020. It is proven by the value of tarithmetic = 3.859 while ttable = 2.306 (tarithmetic > ttable) and strengthened by a significance level of 0.005 < 0.5. Together (simultaneously) the independent variable Earning per Share (EPS) and Net Profit Margin (NPM) has a significant effect on the stock price of PT Indocement Tunggal Prakarsa Tbk. period 2010-2020.F valuecalculated smaller than Ftable (9.675 > 4.26) and strengthened by a significance level of 0.007 < 0.05. The correlation coefficient value is 0.841, which means there is a strong positive effect and the R2 value is 0.707. This means that the influence of the independent variable Earning per Share (EPS) and Net Profit Margin (NPM) on the dependent variable Share Price 70.7%, while the remaining 29.3% is influenced by other variables that are not included in this research model.